Compaction of the Groningen Gas Reservoir Sandstone: Discrete Element Modeling Using Microphysically Based Grain‐Scale Interaction Laws. Issue 9 (22nd September 2021) - Mehranpour, M. H.; Hangx, S. J. T.; Spiers, C. J.
Abstract: Reservoir compaction, surface subsidence, and induced seismicity are often associated with prolonged hydrocarbon production. Recent experiments conducted on the Groningen gas field's Slochteren sandstone reservoir rock, at in‐situ conditions, have shown that compaction involves both poroelastic strain and time independent, permanent strain, caused by consolidation and shear of clay films coating the sandstone grains, with grain failure occurring at higher stresses. To model compaction of the reservoir in space and time, numerical approaches, such as the Discrete Element Method (DEM), populated with realistic grain‐scale mechanisms are needed. We developed a new particle‐interaction law (contact model) for classic DEM to explicitly account for the experimentally observed mechanisms of nonlinear elasticity, intergranular clay film deformation, and grain breakage. It was calibrated against both hydrostatic and conventional triaxial compression experiments and validated against an independent set of pore pressure depletion experiments conducted under uniaxial strain conditions, using a range of sample porosities, grain size distributions, and clay contents. The model obtained was used to predict compaction of the Groningen reservoir. These results were compared with field measurements of in‐situ compaction and matched favorably, within field measurement uncertainties. The new model allows systematic investigation of the effects of mineralogy, microstructure, boundary conditions, and loading path on compaction behavior of the reservoir. It also offers a means of generating a data bank suitable for developing generalized constitutive models and for predicting reservoir response to different scenarios of gas extraction, or of fluid injection for stabilization or storage purposes. Plain Language Summary: In an oil or gas reservoir, located at a few km's depth in the subsurface, pressurized fluid is present in small spaces (pores) between the grains making up the rock. When extracting the fluid, the pressure of the fluid decreases and the reservoir rock will start to feel more of the effective weight of the overlying rock layers. This may lead to elastic (reversible) and inelastic (permanent) compaction of the reservoir by interactions happening at the scale of the individual grains. This reservoir compaction can be observed at the surface through phenomena such as surface subsidence and induced seismicity. Therefore, accurately predicting reservoir compaction, using a numerical model, is crucial to assess these phenomena, and develop safe production strategies. We have developed a grain‐scale, numerical model for the reservoir sandstone rock of the seismogenic Groningen gas field (the Netherlands), based on recent experimental observations. Our model includes realistic grain‐scale interactions, and allows for variations in porosity and mineralogy, as seen in the real rock. With such 'digital samples', in the future it will be possible to extrapolate the limited laboratory experimental data, obtained at specific locations in the reservoir, to the whole field. Key Points: New grain‐contact model for discrete element method is proposed based on microphysical mechanisms observed in Groningen reservoir sandstone The new contact model combined with discrete element modeling predicts nonlinear elastic and inelastic deformation of sandstone It allows systematic investigation of the effects of mineralogy, microstructure, boundary conditions, and loading paths on reservoir behavior